Emerging Markets : Prospects and Challenges - Gudmundsson, Tryggvi; Klyuev, Vladimir; Medina, Leandro; Nandwa, Boaz. (Washington, D.C. : International Monetary Fund, 2022)
This article documents recent developments in emerging markets in the context of the COVID-19 pandemic, assesses their prospects and challenges, and discusses appropriate policy settings for the medium term. It argues that EM policymakers' ability to grapple with an incomplete and uneven recovery will be constrained by high public debt and uncertain inflation prospects as well as external risks surrounding capital flows and exchange rate developments. The paper also discusses potential impact of a tightening in global financial conditions and appreciation of the US dollar that could be triggered by a general increase in risk aversion or a reassessment of the likely path of US monetary policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Banks and Their Policies; EM Inflation; Emerging Markets, COVID-19 and Monetary Policy; Global Outlook; Monetary Policy